Formulation And Physical Quality Testing Of Face Toner Preparations Combining Moringa Leaf Infusion (Moringa Oleifera L.) And Butterfly Pea Flower (Clitoria Ternatea L.) - Sakila Sakila; Annie Rahmatillah; Vivin Marwiyati Rohmana (CV. AFDIFAL MAJU BERKAH, 2026)
Skin aging due to free radicals, pollution, and UV exposure causes dryness, roughness, and decreased elasticity, driving the demand for natural skincare alternatives to replace synthetic toners that often irritate sensitive skin. This study aims to formulate and test the physical quality of face toner from Moringa oleifera L. leaf infusion and Clitoria ternatea L. butterfly pea flower infusion, and determine the optimal formula. This type of development research uses a laboratory experimental approach using a quasi-experimental one-group posttest only design. The population is various potential face toner formulas; samples of three optimal formulas (F1: 3% moringa + 1% butterfly pea, F2: 2% + 2%, F3: 1% + 3%) were replicated three times (n = 9). Instruments include a pH meter, a Brookfield viscometer, a skin analyzer, and microscopic observations; quantitative descriptive data analysis, ANOVA, and post-hoc tests. The results showed that all formulas met the requirements: liquid form, mint scent, pH 6.26-6.50, viscosity 0.53-0.92 mPa.s, homogenous, non-irritating, and increased moisture by 50.81%. F2 was the most optimal with balanced viscosity. In conclusion, this face toner combination provides a stable and safe natural skincare option.